2009
DOI: 10.1007/s00228-008-0604-5
|View full text |Cite
|
Sign up to set email alerts
|

Problem-oriented drug information: physicians’ expectations and impact on clinical practice

Abstract: Purpose Problem-oriented drug information (POD) is a service in which health professionals provide evidencebased answers to clinical questions posed by physicians. The objective of this study was to evaluate the user satisfaction and clinical impact of POD, to investigate predictors for use and to examine the kind of sources physicians search before applying for POD. Methods To evaluate POD, a questionnaire was distributed with problem-oriented answers sent from a drug information centre to physicians during t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
49
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(51 citation statements)
references
References 22 publications
2
49
0
Order By: Relevance
“…While discrepancies among drug-drug interaction databases are well documented, no studies have systematically addressed and compared the transparency of ownership, funding, information, classifications, staff training, and underlying documentation among drug interaction databases [12][13][14][15][16][17][18][19][20]. In the light of the discrepancies between drug interaction databases, such information is imperative to users seeking decision support in order to act upon such with confidence [8,21,22].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…While discrepancies among drug-drug interaction databases are well documented, no studies have systematically addressed and compared the transparency of ownership, funding, information, classifications, staff training, and underlying documentation among drug interaction databases [12][13][14][15][16][17][18][19][20]. In the light of the discrepancies between drug interaction databases, such information is imperative to users seeking decision support in order to act upon such with confidence [8,21,22].…”
Section: Introductionmentioning
confidence: 99%
“…Numerous online drugdrug interaction databases (DIDs) are available as open access or subscription resource [4][5][6][7]. Unfortunately, these often provide little consensus, if not even contradictory advice, much to the frustration of the health-care provider [4,5,[7][8][9]. Studies comparing DIDs have found substantial variations in severity classification and in the availability of underlying references and accessed knowledge resources [4][5][6][7][10][11][12][13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…A DIC in Denmark reported a median time to answer (final answer in contrast to preliminary answer) of 25 days among satisfied physicians and 56 days among unsatisfied physicians 9. In our material, the median time before a written answer was submitted to the questioner was 2 days and 1 day in the periods 1995–2000 and 2001–2006, respectively.…”
Section: Discussionmentioning
confidence: 55%
“…physicians, dentists, nurses, midwives and pharmacists, non-commercial information about drug treatment, drug problems and pharmaceuticals (Hedegaard & Damkier, 2009;Schjøtt et al 2002). The RELIS network is today made up by the four regional drug information centres (DICs) in Norway.…”
Section: Case Reports and Drug Information Centresmentioning
confidence: 99%